Pengaruh Macam Dan Takaran Pupuk Kandang Terhadap Pertumbuhan Adas (Foeniculum vulgare Mill.) - Arief Rakhmad Budi Darmawan (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2015)
The experiment was aimed to study the effect of kinds and rates of manure and also find and gain that treatment resulted in the best growth and development of adas. The experiment was conducted at farmer’s land in Wukirsari village, Sleman regency, special teritory of Yogyakarta.   A factorial experiment of 3x3 factors +1 control was used whereby the treatments were arranged in a randomized complete block design with 3 replicates. The first factor was kind of manure; consisted of 3 kinds, i.e : cow manure, goat manure, chicken manure. The second factor was rates of manure, consisted of 3 levels, i.e : 0,5; 1,0; and 1,5 kg/plant (25, 50, 75 ton/ha). The parameters observed were : plant height, leaf number, stem diameter, leaf area index, shoot root ratio, fresh weight (shoots-roots), dry weight (shoots-roots), net assimilation rate, crop growth rate.    The result of experiment showed that there was no interaction between kinds of manure and their rates except for shoot root ratio 8 weeks after plantation. Three kinds of manure gave the same effect as control on plant growth and development. Rates of manure 1,5 kg/plant gave the best influence to adas growth by increasing total dry weight plant and leaf area index 16 weeks after plantation 52,77 % and 27,48 % compared to control